ZATRUDNIENIE W NIEPEŁNYM WYMIARZE CZASU PRACY - Surdykowska, Barbara (Zeszyty Prawnicze, 2017)
Time-part Employment – Chances and Threats Summary Over the last twenty years, an increasing share of employment across the EU countries has been made up of part time jobs. That is why the growth in part-time employment stands out as a prominent feature of modern labor markets. However, there are still remarkable differences in the relative volumes of the part-time employment share in different countries within the European Union. In recent years, the issue of labor market flexibility has become prominent in the debate over the labor market policy in Europe. The lack of dynamism in the flexibility of the labor markets within the EU countries, often characterized by a height share of long- term unemployment and stringent employment protection legislation, has frequently been blamed for the poor employment performance of the 80s and 90s. An increase in the rate of part-time work has been generally perceived as a positive development as it enables the employers to adjust work hours to the cyclical conditions more easily, facilitates an adjustment of production and labor costs as well as attracts people, who were previously unwilling or unable to work, towards the labor market. But one has to notice that some studies have found that part-time workers earn less than their full time colleagues, my be less likely to receive some benefits and face reduced chances for promotion.